PENGENALAN INTERNET OF THINGS (IOT) KEPADA SISWA DAN SISWI SMA TRIGUNA UTAMA - Hafiz Reja Pratama; Prestu Awensi; Nurul Pernada; Muhamad Yori Romdhoni; Risko Pratama; Muhammad Hafidz Fadhillah; Rangga Dwi Maulana (Abdi Jurnal Publikasi, 2023)
Triguna Utama High School is a Domestic Education Institution under the auspices of the Syarif Hidayatullah Higher Education Foundation. It aims to introduce current technological advances. Triguna Utama High School is under the auspices of the Ministry of Education and Culture. This school has an A accreditation rating obtained in 2019 by implementing the 2013 MIPA curriculum system and holding a learning system for 6 days. Departments at this school are divided into two, namely science and social studies. For this reason, the proposer took the initiative to provide knowledge in the field of Internet of Things technology to Triguna Utama High School students in the form of an introduction to the Internet of Things which functions as a learning tool so that it helps them to get a better learning system to face life in the future and facilitate other forms of activities in Teaching and Learning Activities at Triguna Utama High School.